Redesigning A Service Experience: The Case Study of the New Art Exchange - Amachree, Siya Ibinabobo (2010)
Experience-centric service organizations deliver services in which the customer experience is at the core of the service offering (Zomerdijk and Voss, 2010) the firm dedicates its core resources to making sure that the customer satisfaction is achieved. Experience marketing concentration on the value creation process and how it is achieved through the applications of various skills and knowledge. This paper was looking at developing a new service experience for customers using the New Art Exchange as a case study. The purpose of the study was to explore how experiential marketing and the notion of customer’s value can be applied to redesign a service experience. Questionnaires were given to current customers, potential customers and staff about the New Art Exchange and were conducted by asking respondents a series of questions. Respondents were chosen at random. Semi-structured interviews were also conducted to potential customer and staff at the New art Exchange. Questionnaires and interviews were used to collect data in order to understand and satisfy the aims and objectives of the research aims an objectives. Previous studies have shown that NAE lacks in repeat customer and customer loyalty is quite low. In this study it was found out that the local community are mis-interpreted in terms of value created also customers awareness is quite low. Several difficulties were faced along the way, however the author’s advice to New Art Exchange is adapting. Reason being that consumers attitudes and cultural values are not possible to be changed overnight. But if New Art Exchange is able to close the customer gap created.